An integrated decision-making approach on cutting tools and cutting parameters for machining features considering carbon emissions. Issue 7 (3rd July 2019) - Tian, Changle; Zhou, Guanghui; Lu, Qi; Zhang, Junjie; Xiao, Zhongdong; Wang, Rui
ABSTRACT: Cutting parameters and cutting tools are vital in process planning. Reasonable decision-making of cutting parameters and cutting tools could reduce the processing carbon emissions, time, and cost in machining process. Traditionally, cutting parameter optimization is performed with a preset cutting tool, which limits the potential for carbon emissions savings. In order to globally reduce carbon emissions of machining featuresof parts, this paper provides a new methodology for the integrated optimisation of cutting parameters and cutting tools, where the optimal cutting parameters and cutting tools are identified simultaneously to balance the minimum processing carbon emissions, cost and time for a machining feature of parts. Firstly, a carbon emissions model considering multiple cutting tool flexibilities and corresponding cutting parameters is analyzed and established for a machining feature of parts. Then a multi-objective integration optimisation model of cutting tools and cutting parameters is presented. Thirdly, a NSGA-II algorithm is correspondingly designed to solve the proposed integrated model. Finally, case studies are used to verify the proposed approach. The comparative results show that: i) The integration approach can save more carbon emissions compared with traditional methods; ii) The integrated optimisation methodology can strike a balance among minimum processing carbon emissions, time and cost.